Sequent calculi of first-order logics of partial predicates with extended renominations and composition of predicate complement - Nikitchenko, M.S.; Shkilniak, О.S.; Shkilniak, S.S. (PROBLEMS IN PROGRAMMING, 2020)
We study new classes of program-oriented logical formalisms – pure first-order logics of quasiary predicates with extended renominations and a composition of predicate complement. For these logics, various logical consequence relations are specified and corresponding calculi of sequent type are constructed. We define basic sequent forms for the specified calculi and closeness conditions. The soundness, completeness, and counter-model existence theorems are proved for the introduced calculi.Problems in programming 2020; 2-3: 182-197